The main factor of cluster-economic development - Turgunov A·has·u·eʹrus Turgunovich; Sherkulov Shokhrukh Erkin Ugli; Suvpolatov Ozodjon Alijon Ugli (Peerian Journals Publishing, 2024)
Cluster systems are increasingly recognized as vital tools for economic development in today's world. They foster innovation, enhance competitiveness, and stabilize regional economies by creating a conducive environment for collaboration across industries, trade, and services. The study's findings reveal how clusters contribute to economic growth, influence innovation processes, and bolster overall economic stability
Keywords: Cluster systems; economic development; innovation; competitiveness